抗ＯＳＭＲΒ抗体の送達による皮膚疾患又は障害の治療 (2021)
本発明は、とりわけ、掻痒性又は炎症性皮膚疾患若しくは障害、又は疾患若しくは障害に関連する掻痒症を抗ＯＳＭＲβ抗体で治療する方法を提供し、アトピー性皮膚炎、慢性腎臓病関連掻痒症、尿毒症性掻痒症又は結節性痒疹、慢性特発性掻痒症、慢性特発性蕁麻疹、慢性自発性蕁麻疹、皮膚アミロイドーシス、慢性単純性苔癬、尋常性乾癬、扁平苔癬、炎症性魚鱗癬、肥満細胞症及び水疱性類天疱瘡に関連する掻痒症を治療する方法を含み、治療を必要とする対象に、対照に比べて、疾患若しくは障害の一つ以上の症状を改善し、安定にし、若しくは低減させるのに充分な治療有効用量及び治療期間の投与間隔で抗ＯＳＭＲβ抗体を投与するステップを含む。 The present invention provides, among other things, methods of treating pruritic or inflammatory skin diseases or disorders, or pruritus associated with a disease or disorder, with an anti-OSMRβ antibody, including methods of treating pruritus, associated with atopic dermatitis, chronic kidney disease-associated pruritus, uremic pruritus or prurigo nodularis, chronic idiopathic pruritus, chronic idiopathic urticaria, chronic spontaneous urticaria, cutaneous amyloidosis, lichen simplex chronicus, plaque psoriasis, lichens planus, inflammatory ichthyosis, mastocytosis and bullous pemphigoid, comprising a step of administering to a subject in need of treatment an anti-OSMRβ antibody at a therapeutically effective dose and an administration interval for a treatment period sufficient to improve, stabilize or reduce one or more symptoms of the disease or disorder relative to a control.